2022
DOI: 10.3390/ijms24010420
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Channels and Itch

Abstract: Transient Receptor Potential (TRP) channels are multifunctional sensory molecules that are abundant in the skin and are involved in the sensory pathways of itch, pain, and inflammation. In this review article, we explore the complex physiology of different TRP channels, their role in modulating itch sensation, and their contributions to the pathophysiology of acute and chronic itch conditions. We also cover small molecule and topical TRP channel agents that are emerging as potential anti-pruritic treatments; s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…It has been found that many other factors, including mast cell mediators, neuropeptides, neurotrophins, and proteases have many effects on the skin, mainly participating in the occurrence and development of itching [ 42 ]. Although the exact mechanism of itch has not been fully elucidated, it is clear that a complex crosstalk between the stratum corneum, keratinocytes, T cells, eosinophils, basophils, mast cells, and nerve fibers plays an important role in the initiation and maintenance of pruritus [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that many other factors, including mast cell mediators, neuropeptides, neurotrophins, and proteases have many effects on the skin, mainly participating in the occurrence and development of itching [ 42 ]. Although the exact mechanism of itch has not been fully elucidated, it is clear that a complex crosstalk between the stratum corneum, keratinocytes, T cells, eosinophils, basophils, mast cells, and nerve fibers plays an important role in the initiation and maintenance of pruritus [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…68,69 Furthermore, patents for small molecule candidates targeting TRPA1 channels have been filed by several drug-developing pharma companies including Eli Lilly, Genentech/Roche, Algomedix Inc., Glenmark, Boehringer Ingelheim, Almirall S.A., Orion Corp., EA Pharm Co. and Mandom Corp. TRPA1 antagonists HC-030031 and GRC-17536 are effective anti-tussive mediators. 70,71 Recent findings have revealed GDC-0334, a TRPA1 antagonist to possess better target engagement in human subjects. In preclinical studies involving respiratory disease models, GDC-0334 exhibited inhibition toward edema formation, smooth muscle hyperreactivity, and cough response.…”
Section: Trpa1 As a Drug Targetmentioning
confidence: 99%
“…Several phase I and II clinical trials of TRPV1 antagonists have been conducted to examine their potential usefulness as analgesics. 2123 David Julius has received the Nobel Prize in Physiology or Medicine in 2021 for the identification of transient receptor potential (TRP) and transient receptor-like protein functions. 24,25 The discovery of the molecular transducers underlying the senses of temperature and touch increased greatly our understanding of how the nervous system encodes sensory information.…”
Section: Introductionmentioning
confidence: 99%